1992
DOI: 10.1210/mend.6.10.1448113
|View full text |Cite
|
Sign up to set email alerts
|

Ligands induce conformational changes in the carboxyl-terminus of progesterone receptors which are detected by a site-directed antipeptide monoclonal antibody.

Abstract: We have prepared a monoclonal antibody, C-262, to a synthetic peptide that contains the carboxy-terminal 14 amino acids from progesterone receptors (PR). This sequence is 100% conserved in all species of PRs that have been cloned to date, suggesting that this antibody will recognize all mammalian and avian PR. The C-262 antibody recognizes both native and denatured forms of the receptor. However, it does not recognize PR when they are bound to the hormone agonists progesterone or R5020. Surprisingly the antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…In an experiment with a larger amount of unlabeled androgen receptors, obtained from LNCaP cells, it was shown that the interaction of HSP90 with an immunopurified AR is disturbed upon a salt wash, whereas ligand binding remained (dissociation of HSP90 shown in Fig. 3, lane [15][16][17][18]. Strikingly, when the in vitro produced 35 Slabeled AR on the affinity matrix was liganded with an antiandrogen, trypsinization now resulted in the formation of a 29-kDa fragment (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In an experiment with a larger amount of unlabeled androgen receptors, obtained from LNCaP cells, it was shown that the interaction of HSP90 with an immunopurified AR is disturbed upon a salt wash, whereas ligand binding remained (dissociation of HSP90 shown in Fig. 3, lane [15][16][17][18]. Strikingly, when the in vitro produced 35 Slabeled AR on the affinity matrix was liganded with an antiandrogen, trypsinization now resulted in the formation of a 29-kDa fragment (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The model argues that agonists and antagonists recognize distinct regions of the ligand binding domain. Antagonists induce an incomplete conformational change that results in dimerization and DNA binding, but leave the C terminus of the ligand binding domain in a form still available for protease (11) and antibody recognition (14,15). As a result, a surface repressor function is not removed and the receptor is not able to induce transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the cell and the promoter context, RU486 can function as either an agonist or an antagonist. Accumulating evidence reveals that mixed antagonists induce a unique PR conformation that is different from those conformations induced by either pure agonists or pure antagonists (22), and that ligand-induced conformational changes in a receptor may regulate the interactions of steroid receptors with coregulators (25,28). To explain the capacity of mixed antagonists to manifest different activities in different cellular contexts, we hypothesized that a differential ratio of coactivator to corepressor can directly modulate the ability of RU486 to activate transcription in different cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, progesterone and RU486 appear to contact noncoincident, but overlapping, amino acids in the ligand-binding domain (LBD) of PR (22)(23)(24). The precise manner in which multiple conformations of PR induced by SPRMs affects its agonist or antagonist activity is open to question.…”
mentioning
confidence: 99%